Reuse Wastewater Effluent of PT Krakatau Steel as Alternative Raw Water Source for Clean Water Production in PT Krakatau Tirta Industri (The Indonesian Journal of Business Administration, 2013)
PT Krakatau Tirta Industri is a subsidiary company of PT Krakatau Steel, was established on February 28, 1996, which the main business is providing and distributing clean water for domestic and industrial customer in Cilegon City. PT KTI started commercial operations in 1978 as part of Division Water Supply and Distribution PT Krakatau Steel. PT KTI has installed capacity 2.000 liter/second with current utilization reaches 60%. Currently PT Krakatau Tirta Industri faced the strategic problems related water supply services such as (i) the development planning of PT Krakatau Steel as holding company (ii) the potential development in industrial and domestic sector in Cilegon City and surrounding (iii) the limitation of availability raw water sources in Cilegon City and reliability of potential capacity can be taken from existing raw water sources, Cidanau River, (iv) government regulation related to water sources management, (v) potential development in national market for drinking water sector referred to Government for MDGs Program at 2015. All strategic problem impact to the water needs of consumers exceeded the capacity of water production from PT KTI. Therefore, in anticipation of water shortages need to increase the capacity of production process and the availability of sources of raw water. Some potential alternative raw water source as follow (i) Optimization Cidanau River (ii) expansion Krenceng DAM (iii) reuse effluent wastewater PT Krakatau Steel (iv) seawater Desalination Treatment Plant.Â  From all alternatives used the weighted method then the first program for realization is Reuse Effluent Wastewater Krakatau Steel. The mainstay flow of water source from Krakatau Steel is 280 liter/second. At the first stage the installation will be design with flow 150 liter/second, and expected will produce clean water 100 liter/second, which the product fulfill the standard from Ministry of Health No. 416/1990, suitable with the product from existing production. The treatment process is different from the existing production processes; there will be applied combined technology, conventional and membrane technology. The location of installation will be taken on land owned by PT Krakatau Steel, near from raw water sources and existing distribution pipeline network.Â Keywords: raw water, effluent wastewater, reuse, water supply.Â